Acoustic Playback Stimulus Experiment to Study Mating Behavioral Responses of Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) - Ayu Purnamasari; Susilo Hadi; Suputa Suputa (AGRIVITA, Journal of Agricultural Science, 2022)
The melon fly, Bactrocera cucurbitae is serious pest attacks fruits and vegetables. The manipulation of male mating behavior that displays acoustic signals is one of the steps in the behavior-based control strategy of B. cucurbitae. The first study period determines the courtship song characteristics, frequency, and occurrence time. The recording was carried out when B. cucurbitae was mated using recording devices at 04.00–07.00 pm. The results show three sounds produced before copulation, namely, calling, courtship, and stimulating, with frequencies 274.30 ± 3.29 Hz, 284.65 ± 2.00 Hz, and 304.36 ± 1.82 Hz. B. cucurbitae courtship song began at 04.00–06.26 pm. The second study was performed to determine the effect of experimental acoustic playback stimulus on the selection of mating pairs by females. The acoustic playback stimulus is made synthetically by playback of two channels, namely, calling and courtship sounds, with frequencies of 274 and 284 Hz at a sound pressure level (SPL) of 85 dB. The experimental results of acoustic playback stimulus show that the sexual behavior of female B. cucurbitae was disrupted and marked by the decreased number of copulations during SPL is high, resulting in the overlapping calling and courtship sounds frequencies that impair signal detection.